The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11064-010-0376-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alpha-Ketoglutarate on Neurobehavioral, Neurochemical and Oxidative Changes Caused by Sub-Chronic Cyanide Poisoning in Rats

Abstract: Recent studies revealed that alpha-ketoglutarate (A-KG) alone or with sodium thiosulfate (STS) provide significant protection against acute and sub-acute cyanide poisoning in rodents. This study addresses the protective effect of A-KG and/or STS in sub-chronic (90 days) cyanide poisoning. Wistar rats were divided into seven groups (n = 10): Control animals, potassium cyanide (KCN) A-KG, STS, KCN ? A-KG, KCN ? STS and KCN ? A-KG ? STS. Spontaneous motor activity and motor coordination were recorded every 15th d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
4
12
0
Order By: Relevance
“…Thus, the combined administration of AKG and SNP partially prevented antioxidant enzyme inactivation and oxidative damage of lipids which agrees with previous studies (Tulsawani et al, 2005;Bhattacharya et al, 200;Mathangi et al, 2011).…”
Section: Alpha-ketoglutarate Prevents Oxidative Damages In Snp-rearedsupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, the combined administration of AKG and SNP partially prevented antioxidant enzyme inactivation and oxidative damage of lipids which agrees with previous studies (Tulsawani et al, 2005;Bhattacharya et al, 200;Mathangi et al, 2011).…”
Section: Alpha-ketoglutarate Prevents Oxidative Damages In Snp-rearedsupporting
confidence: 92%
“…The protective effects of AKG are considered to be due to the capability of the carbonyl groups on AKG to interact with cyanide to yield less toxic cyanohydrin intermediates (Niknahad et al, 1994, Mitchell et al, 2013. In the line with this, the potential of AKG to prevent depletion of antioxidant defenses or counteract the increase in levels of oxidative stress markers during acute or sub-chronic cyanide poisoning was demonstrated (Tulsawani et al, 2005;Tulsawani and Bhattacharya, 2006;Bhattacharya et al, 2009;Mathangi et al, 2011). Furthermore, several studies reported that the protective effects of AKG against various toxic agents in vitro and in vivo could be related with its direct antioxidant action (Sokołowska et al, 1999;Murugesan and Subramanian, 2006;Kovalenko et al, 2011;Niemiec et al, 2011;Long and Halliwell, 2011).…”
Section: Alpha-ketoglutarate (Akg) Is An Important Intermediate In Thmentioning
confidence: 98%
See 3 more Smart Citations